How Worlds are Made: Literatures, Translation, and the Question of the Universal - Arenberg, Meg (Research in African literatures, 2025)
Weaving the work of Eileen Julien on the “extroverted” African novel throughout, this article considers arguments around the relationship of African literature to the notion of literary universality, with special attention to the position of African languages within these arguments. Novels by Kenyan writers Ngũgĩ wa Thiong’o and Yvonne Adhiambo Owuor and theoretical interventions by Walter Benjamin, Edouard Glissant, and Souleymane Bachir Diagne in particular are used to develop strategies for reading moments of contact between English and African languages in Anglophone African novels as central to the pursuit of a universality that is neither totalizing nor Eurocentric.